Wet Cupping (al-hijama) for Mental Health: A Systematic Review - Yasemin Ucun (MEDrang Inc., 2022)
This systematic review aimed to evaluate the effects of wet cupping on the treatment of mental illness. A total of 2,670 studies were retrieved using PubMed, Cochrane Library, Web of Science, Google Scholar, and Science Direct databases, and of these, 2,661 were excluded due to not meeting the inclusion criteria. There were 9 articles included in this review including 1,124 individuals who received wet cupping. Mental health was explored in, those who had migraines, metabolic syndrome, smoking addiction, post-traumatic stress, chronic medical disease, and depression. As an intervention procedure, the triple S technique was used in all studies. Only 3 studies reported that none of the participants complained of adverse events during or after the cupping therapy. In all studies, wet cupping was reported to be effective in reducing psychological symptoms. However, there are few randomized controlled trials testing the e?ectiveness of wet cupping in the treatment of mental health, and most are of poor quality. Therefore, more rigorous studies are required before the effectiveness of wet cupping for the treatment of mental illness can be determined.